New method for mapping radial turbines exposed to pulsating flows. (1st November 2018) - Liu, Zheng; Copeland, Colin
Abstract: In this paper, a new method for mapping radial turbines will be demonstrated and shown to be superior to the standard approach typical to gas-stand laboratories. This is especially true in situations where the turbine is exposed to unsteady flow as is the case in the turbocharger. In order to generate realistic pulsating flows in a laboratory environment, a pulsation generator, including a cylinder head of three cylinders, was designed in the University of Bath. This study demonstrated that the standard mapping approach is not able to capture the period of negative power since it is a purely transient phenomenon. Therefore, a new approach of generating maps is suggested based on extrapolating data generated from the unsteady measurement resulting from the pulse rig. This method is then tested by demonstrating its ability to recreate the real pulsating behaviour and ability to predict compressor power. In this study, turbine instantaneous power measurements were conducted under both three-cylinder mode and two-cylinder modes. Negative turbine power was measured during the trough of a pulse, indicating that both turbine and compressor absorb energy from the rotating inertial during that period. This study found the negative turbine work can take up approximately 15% of turbine net work under 20 Hz pulses. This percentage is even more once one or more cylinders are deactivated. This paper highlighted that if not considering the negative efficiency, it will result in an error shaft speed prediction, and thereby may affect the overall performance of turbocharger even engines.